Glycosylation and the global virome. Issue 1 (21st October 2022) - Pegg, Cassandra L.; Schulz, Benjamin L.; Neely, Benjamin A.; Albery, Gregory F.; Carlson, Colin J.
Abstract: The sugars that coat the outsides of viruses and host cells are key to successful disease transmission, but they remain understudied compared to other molecular features. Understanding the comparative zoology of glycosylation ‐ and harnessing it for predictive science ‐ could help close the molecular gap in zoonotic risk assessment.